Factors That Shape Design Thinking - Gray, Colin M. (Design and Technology Education: An International Journal, 2013)
A wide range of design literature discusses the role of the studio and its related pedagogy in the development of design thinking. Scholars in a variety of design disciplines pose a number of factors that potentially affect this development process, but a full understanding of these factors as experienced from a critical pedagogy or student perspective is lacking. In this study, the experiences of six first-year design students were examined as they evolved in their conceptions of design. Data was collected during a series of three interviews. Analysis of data confirmed and recontextualized factors identified in the literature. Additional factors relating to group work, culture shock, critique, individual versus group identity, and the design influence of professors, mentors, and curricula are identified and reported. Opportunities for future research are identified.